The COVID-19 pandemic and stock liquidity: Evidence from S&P 500 - Chebbi, Kaouther; Ammer, Mohammed Abdullah; Hameed, Affan (The Quarterly review of economics and finance, 2021)
•We empirically investigate the impact of the COVID-19 pandemic on the stock liquidity of S&P 500 firm.•There exists a negative association between COVID-19 (as measured by the daily growth in the numbers of cases and deaths) and stock liquidity.•These results imply the COVID-19 pandemic decreases firm liquidity.•Our findings remain robust to the use of an alternative proxy for liquidity and to alternative estimation approaches.•Further analysis reveals a significant difference in liquidity between sectors. This study examines the influence of the COVID-19 pandemic on the stock liquidity of S&P 500 firms. We construct a daily data set for stock liquidity and the numbers of COVID-19 reported cases and deaths for the period from 1 January 2020 to 31 December 2020. The regression results show that there is a significant negative relationship between COVID-19 (as measured by the daily growth in the numbers of cases and deaths) and stock liquidity, implying that the COVID-19 pandemic decreases firm liquidity. Furthermore, our analysis reveals a significant difference in liquidity between sectors. In addition, our results remain robust to the use of an alternative proxy for liquidity and to alternative estimation approaches. The results of this study will allow key players in the stock market to recognize and forecast the behavior of stock liquidity during periods marked by pandemic diseases.